Development of ECG home monitoring system - Rafiq, Sarah; Alam, A. H. M. Zahirul; Islam, Md. Rafiqul (IEEE, 2017)
Nowadays, the cardiovascular diseases have become one of the leading causes of death. The ECG signal comprises of the electrical signals of the heart that can be used to reveal the heart’s condition. This could indicate early health warnings and help prevent fatal incidents. In this paper, a 3-electrodes home ECG monitoring system has been developed and designed to detect the condition of the heart at instant without going to the hospital for precautionary measures. The developed ECG system can be integrated to Wi-Fi LAN or mobile Bluetooth to communicate with doctor for immediate advice. The wet electrodes have been used for acquiring ECG signals of different age groups of people to verify the effectiveness of the system. The acquired ECG signals were verified using the persons’ previous medical history.